2007
DOI: 10.1124/dmd.107.014753
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3A-Dependent Metabolism of a Potent and Selective γ-Aminobutyric AcidAα2/3 Receptor Agonist in Vitro: Involvement of Cytochrome P450 3A5 Displaying Biphasic Kinetics

Abstract: ABSTRACT:In vitro metabolism studies were conducted to determine the human cytochrome P450 enzyme(s) involved in the biotransformation of 7-(1,1-dimethylethyl)-6-(2-ethyl-2H-1,2,4-triazol-3-ylmethoxy)-3-(2-fluorophenyl)-1,2,4-triazolo[4,3b]pyridazine (TPA023), a selective agonist of human ␥-aminobutyric acid A receptor ␣2 and ␣3 subunits. Incubation of TPA023 with NADPH-fortified human liver microsomes resulted in the formation of t-butyl hydroxy TPA023, N-desethyl TPA023, and three minor metabolites. Both t-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…3). Both the t ‐butyl hydroxylation and the N ‐deethylation reactions in human liver microsomes were greatly inhibited by CYP3A‐specific antibodies and inhibitors, with CYP3A4 rather than CYP3A5 playing the major role in TPA023 metabolism (Ma et al 2007). The M1 and M2 metabolites of TPA023 were also found in vivo in rat as well as human but are not considered to play a pharmacological role based on their poor blood‐brain barrier penetration as well as, in the case of the M2 metabolite, lower affinity for GABA A receptors than the parent.…”
Section: Metabolism Of Tpa023 and α5iamentioning
confidence: 99%
See 1 more Smart Citation
“…3). Both the t ‐butyl hydroxylation and the N ‐deethylation reactions in human liver microsomes were greatly inhibited by CYP3A‐specific antibodies and inhibitors, with CYP3A4 rather than CYP3A5 playing the major role in TPA023 metabolism (Ma et al 2007). The M1 and M2 metabolites of TPA023 were also found in vivo in rat as well as human but are not considered to play a pharmacological role based on their poor blood‐brain barrier penetration as well as, in the case of the M2 metabolite, lower affinity for GABA A receptors than the parent.…”
Section: Metabolism Of Tpa023 and α5iamentioning
confidence: 99%
“… The major metabolic pathways of TPA023 and α5IA. Metabolism of TPA023 proceeds via the predominantly CYP3A4‐mediated t ‐butyl hydroxylation and N ‐deethylation (Ma et al 2007) whereas the single major metabolite of α5IA is the hydroxymethyl isoxazole. …”
Section: Metabolism Of Tpa023 and α5iamentioning
confidence: 99%
“…20) In addition, it has been reported that whether cytochrome b 5 is added by supplementation or coexpression also affects the metabolic activity. Ma et al 53) reported that the t-butyl hydroxylation and N-demethylation activities of TPA023 obtained by cytochrome b 5 -coexpressed CYP3A5 are higher than those of cytochrome b 5 -supplemented CYP3A5. Similarly, CYP3A4 coexpressed with cytochrome b 5 results in higher catalytic activity toward ifosfamide Ndechloroethylation than that of cytochrome b 5 -supplemented CYP3A4; this effect was greater than that for CYP3A5.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most of the V max and V max /K m values for dehydrogenation of many of the dihydropyridine calcium antagonists, such as benidipine, felodipine, and nifedipine, and steroid hydroxylation, such as testosterone 6β-hydroxylation and estradiol 2-or 4-hydroxylation, mediated by CYP3A5, are lower than those mediated by CYP3A4, whereas the K m values for CYP3A5 are higher than those for CYP3A4. 20,[27][28][29]41) Similarly, the CYP3A5- 53) Bold: The ratio of the parameters for CYP3A5 and CYP3A4 was less than 0.5 times or more than 2 times. a) Benidipine, felodipine, nifedipine, and nitrendipine.…”
Section: Metabolic Activity Of Cyp3a4 and Cyp3a5mentioning
confidence: 99%
“…CYP2B6 functional polymorphisms are highly prevalent in several African [32][33][34][35] and Asian countries. 35,36 In most of these countries, artemisinin-based combination therapy has been used as first-line treatment for acute uncomplicated P. falciparum malaria. The CYP2B6*9 allele is commonly found in all ethnic groups, but more frequently in Hispanics compared with African-Americans, Caucasians, and Asians.…”
Section: Discussionmentioning
confidence: 99%